Comparison between minimally invasive plate osteosynthesis and open plating for proximal humeral fractures: a meta-analysis. (27th September 2018) - Zang, Jia-cheng; Du, Jing-jing; Li, Chen; Wang, Jing-bo; Ma, Xin-long
Aim: We conducted this meta-analysis for comparing the efficacy and safety in proximal humeral fractures by treatment minimally invasive plate osteosynthesis and open plating.Methods: The potential academic literature were identified from the Cochrane Library, Springer, PubMed, Embase and ScienceDirect. Pooled data were analyzed by RevMan 5.1.Results: Seven studies marched with the inclusion criteria. Meta-analysis showed the significant differences in terms of blood loss, operative time, length of hospital stays and constant score between two groups. No significant differences were found in time to union, the union rate and complications.Conclusion: Minimally invasive plate osteosynthesis in proximal humeral fractures provided significantly shorter operative times, length of hospital stays, less blood loss and better clinical outcomes without increasing complications.